The Effect of Photobiomodulation on the Depth of Anesthesia During Endodontic Treatment of Teeth With Symptomatic Irreversible Pulpitis (Double Blind Randomized Clinical Trial) - Ghabraei, Sholeh; Chiniforush, Nasim; Bolhari, Behnam; Aminsobhani, Mohsen; Khosarvi, Abbas (Journal of Lasers in Medical Sciences, 2017)
Introduction: Achieving appropriate anesthesia in patients with symptomatic irreversible pulpitis in mandibular molars during endodontic treatment is always one of the most challenging aspects. Photobiomodulation (PBM) has been used in dentistry due to its anti-inflammatory properties and regenerative effects. This study evaluates the effects of PBM in the depth of anesthesia in inferior alveolar nerve block. Methods: In this randomized clinical trial, 44 patients requiring endodontic treatment in lower molar, left or right were selected, half of them were randomly treated with PBM therapy. Laser irradiation by 980 nm diode laser with a single dose (15 J/cm2, for 20 seconds) before anesthesia was performed at the buccal aspect. Inferior alveolar nerve block was performed once. Success was defined as no or mild pain (no need for any supplemental injection), based on the visual analogue scale during access cavity preparation. Results were evaluated using SPSS software. Results: The results of this study showed that the necessity for supplemental injection was lower in the group receiving laser than in the group without laser (P = 0.033). The mean pain intensity during dentin cutting was lower in the group receiving laser than in the group without laser (P = 0.031). Also, the mean pain intensity during pulp dropping was lower in the group receiving laser, than the group without laser (P = 0.021). Conclusion: Based on the results of this study, it seems that the application of PBM before anesthesia is effective on increasing depth of anesthesia.